Association between body fat and sarcopenia in older adults with type 2 diabetes mellitus: A cross-sectional study - Sun, Lina; Fu, Junling; Mu, Zhijing; Duan, Xiaoye; Chan, Piu; Xiu, Shuangling (Frontiers in Endocrinology, 2023)
Objectives: To investigate the association between body fat (BF%) and sarcopenia in older adults with type 2 diabetes mellitus (T2DM) and potential link with increased levels of inflammatory indicators and insulin resistance. Methods: A total of 543 older adults with T2DM were included in this cross-sectional study. Appendicular skeletal muscle (ASM), handgrip strength and gait speed were measured to diagnose sarcopenia according to the updated Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Body composition data were tested using dual-energy X-ray absorptiometry (DEXA). Levels of serum high-sensitive C-reactive protein (hs-CRP), interleukin-6, fasting blood insulin (FINS), hemoglobin A1c (HbA1c), 25-hydroxyvitamin D3 [25(OH) D3] were also determined. Results: The prevalence of sarcopenia in all participants was 8.84%, of which 11.90% were male and 5.84 % females. The Pearson’s correlation analysis revealed that BF% was negatively correlated with gait speed in men and women (R =-0.195, P=0.001; R = -0.136, P =0.025, respectively). After adjusting for all potential confounders, sarcopenia was positive associated with BF% (male, OR: 1.38, 95% CI: 1.15–1.65, P< 0.001; female, OR: 1.30, 95% CI: 1.07–1.56, P=0.007), and negatively associated with body mass index (BMI) (male, OR: 0.57, 95% CI: 0.44–0.73, P<0.001; female, OR: 0.48, 95% CI: 0.33–0.70, P<0.001). No significant differences were found in hs-CRP, interleukin-6, and insulin resistance between older T2DM adults with and without sarcopenia. Conclusion: Higher BF% was linked to an increased risk of sarcopenia in older adults with T2DM, suggesting the importance of assessing BF% rather than BMI alone to manage sarcopenia.